Evaluation of the Coordination of the 250 kVA Distribution Transformer Protection System Between Lightning Arrester and Grounding System - M. Ramadhany Aprianto; Dian Eka Putra; Raden Ahmad Yani; Choirul Rizal; Nofiansah (Journal of Renewable Energy, Electrical, and Computer Engineering, 2026)
This case study evaluates the coordination of the 250 kVA distribution transformer protection system at the PE 501 substation, including analysis of the lightning arrester and grounding system. The research uses field measurement (grounding resistance using the three-point fall-of-potential method) and mathematical computation based on standard equations. The results show that the polymer arrester with a rated voltage of 16 kV and a discharge current of 4.2 kA meets the protection criteria, with a protection factor of 23.44%. The installation of the arrester at a distance of 3.7 meters from the transformer, within the maximum limit of 3.8 meters, ensures the effectiveness of surge voltage attenuation. The grounding system, using two rod electrodes, successfully reduced resistance from 9.688 ohms to 4.84 ohms, meeting the PUIL 2011 standard (<5 ohms). However, regular monitoring is required to ensure the system's performance remains optimal, especially in lightning-prone areas. Recommendations include routine checks of grounding resistance, evaluation of arrester performance, and upgrading the grounding system using modern technology. This study highlights the importance of coordination between arresters and grounding to protect transformers from overvoltage disturbances.